Formation of copper nanoparticles on poly(thymine) through surface-initiated enzymatic polymerization and its application for DNA detection. Issue 16 (21st August 2015) - Hu, Weiwen; Ning, Yong; Kong, Jinming; Zhang, Xueji
<x xml:space="preserve">Abstract</x> A DNA biosensor using polyT-templated CuNPs as the fluorescent probe and SIEP as the signal amplification strategy is proposed.